Notary’s Ethics Sanctions for Violations of the Associations’s Code of Ethics - Siti Rohani; Amiruddin; Muhaimin (MultiTech Publisher, 2024)
This research discusses the forms of violating the code of ethics carried out by notaries as well as the categories of sanctions given based on the type of violation. The type of research used is normative legal research using statutory, conceptual and case approaches. Data collection methods using document study include book laws and other written works and deductive conclusions. Based on the research results, firstly, the forms of violations committed by notaries include: not having good morals, morals and personality by committing adultery; does not respect and uphold the honor and dignity of the Notary's position and does not behave honestly, impartially, and is not trustworthy because he commits an act of falsifying a deed which results in one of the clients benefiting; not prioritizing service to the needs of society and the State because it is more profitable for the individual; carrying out unfair competition against other notaries by withholding client documents and setting a lower honorarium than other notaries. Second, the categories of sanctions based on the type of violation are divided into 2, namely light sanctions and heavy sanctions. Sanctions of reprimand, warning sanctions are in the category of sanctions for minor violations, temporary suspension, honorable termination and dishonorable termination from membership include the category of sanctions for serious violations